Investigations of N@C60 and N@C70 stability under high pressure and high temperature conditions - Iwasiewicz-Wabnig, A; Porfyrakis, K; Briggs, G; Sundqvist, B (2009)
Endohedral fullerenes encapsulating single nitrogen atoms (N@C60 and N@C70) are spin active, due to the presence of unpaired nitrogen electron spins. High reactivity of nitrogen leads to a poor stability of these molecules at elevated temperatures, drastically restricting possibilities of their chemical treatment. In this study, N@C60 and N@C70 in toluene solutions were subjected to high pressure (HP) up to 0.8 GPa and annealed for 1, 2, 10 or 24 h, at either room or elevated temperatures. In each case the number of surviving molecules was evaluated based on the relative spin counts of ex situ EPR spectra obtained before and after the treatment. The enhanced thermal stability of N@C60 and N@C70 under HP conditions is attributed to inhibited formation of azabridges, which under normal pressure facilitate the escape of nitrogen from the fullerene cage. © 2009 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.